Dravčani: Zgodovina Dravcev in njenih prebivalcev - Hojnik, Janja (University of Maribor Press, 2025)
Dravčani: The History of the Village Dravci and Its Inhabitants. The book portrays the history of the village of Dravci in the Haloze region. Archaeological findings indicate that the village was inhabited as early as the Stone and Copper Ages, as well as during the Roman Empire. In the Middle Ages, the Dravci area was part of a border region contested by Austrian and Hungarian rulers. Borl Castle, which overlooks Dravci, was built by the Hungarians no later than the 13th century. For much of its history, Dravci was part of the Borl estate (Ankenstein), with two periods when it belonged to the Zavrč (Sauritsch) estate. The first known written mention of Dravci dates back to 1542, when the village was recorded in the Borl estate register. The book documents all individuals for whom archival records could be found indicating residence in the village. Based on this data, the book presents life in the village and the history of Dravci families over time, covering at least the last three centuries. It examines the village’s administrative placement, judicial matters, infrastructure issues, the education of the inhabitants, their involvement in religious life, care for social and health issues, economic activities, and the dynamics between men and women over time. It is evident that the village was predominantly made up of medium-sized landowners and was highly self-sufficient. Life expectancy has increased, and mortality rates have decreased. Despite this, the population of the village continues to decline.